ENALAPRIL MALEATE IN TREATMENT OF ARTERIAL HYPERTENSION IN PATIENTS WITH DIABETES MELLITUS - L. I. Katelnitskaya; G. O. Trenyova (Российский кардиологический журнал)
The study includes 25 patients with arterial hypertension (AH) and 25 patients with non-insulin dependent diabetes mellitus (NIDDM) combined with AH. All patients, at baseline and 2 weeks following treatment with enalapril maleate (Enam, Dr.Reddy’s Laborotories Ltd., India), general clinical examination as well as measurement of blood glucose, cholesterol, lipoproteins, triglycerides; conventional echo and evaluation of vasomotoric function of endothelium by D.S. Celermajer’s method. We have shown that even with blood pressure decreasing to the same levels, endothelium-dependent relaxation improved best in the group with NIDDM whereas LV diastolic function dynamics did not differ significantly; those changes having strong correlation to the levels of serum lipoproteins and triglycerides. The results suggest enalapril maleate not just a nephropotective measure in patients with AH and NIDDM, but also as a medication for heart protection in such patients.